2011
DOI: 10.1103/physrevlett.107.164503
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamics of Self-Sustained Supersonic Reaction Waves: Fickett’s Detonation Analogue

Abstract: The present study investigates the spatio-temporal variability in the dynamics of self-sustained supersonic reaction waves propagating through an excitable medium. The model is an extension of Fickett's detonation model with a state dependent energy addition term. Stable and pulsating supersonic waves are predicted. With increasing sensitivity of the reaction rate, the reaction wave transits from steady propagation to stable limit cycles and eventually to chaos through the classical Feigenbaum route. The physi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 13 publications
2
30
0
Order By: Relevance
“…The one-dimensional, inviscid scalar Burgers equation with a source term was proposed by Fickett [15] and Majda [36] as an analog to the reactive Euler equations in order to explore detonation dynamics. In recent years, study of this scalar analog system has generated a number of interesting results, including the existence of pulsating, chaotic solutions [48,27,61,14]. The study of Mi & Higgins [38] was a precursor to the present study using the inviscid Burgers equation with periodically spaced δ-function sources that were triggered by the passage of the leading shock front.…”
Section: Discussionmentioning
confidence: 95%
“…The one-dimensional, inviscid scalar Burgers equation with a source term was proposed by Fickett [15] and Majda [36] as an analog to the reactive Euler equations in order to explore detonation dynamics. In recent years, study of this scalar analog system has generated a number of interesting results, including the existence of pulsating, chaotic solutions [48,27,61,14]. The study of Mi & Higgins [38] was a precursor to the present study using the inviscid Burgers equation with periodically spaced δ-function sources that were triggered by the passage of the leading shock front.…”
Section: Discussionmentioning
confidence: 95%
“…where t is time, and thermicity is defined as Figure 1 illustrates the structure of the self-supported detonation wave [17]. The detonation structure consists of pressure waves originating from the back (left), travelling along characteristics dx/dt = ρ and amplifying according to the characteristic equation (4).…”
Section: Model: Reactive Burger's Equationmentioning
confidence: 99%
“…The model neglects the rear facing pressure waves of gas dynamics, hence significantly simplifying the mathematical complexity of the description. The model retains the important physics of reactive compressible flows and its complex dynamics, namely that pressure waves receive amplification, modulated by the local rate of energy release, and can form shocks [17]. Fickett has already demonstrated how the model can reproduce the complex steady structure of eigenvalue detonations in the presence of one exothermic and one endothermic reaction [16].…”
Section: Introductionmentioning
confidence: 99%
“…shocks and shock waves) have counterparts in the analog systems as well. Recently it was also shown that the Fickett model applied to a spatially uniform reactive media governed by a two-step chemical kinetics [6] has the ability to reveal some key nonlinear dynamics also observed in the Euler system [7], including the period-doubling bifurcation leading to chaos. Using a similar approach, detonation instability originated from the inclusion of a loss term such as friction or curvature can also be recovered [8].…”
Section: Introductionmentioning
confidence: 98%